The Effects of Haram Food on Human Emotional and Spiritual Intelligence Levels - Farid, Miftah; Basri, Hasan (Indonesian Journal of Halal Research, 2020)
Muslims are taught to eat clean and safe food. Islam is very concerned about the source and cleanliness of food, how to cook, how to serve, how to eat to how to dispose of leftovers. The concept of Islam in food is actually the same as the concept of Islam in other respects, namely the concept that maintains the safety of the soul, body, and mind. Halal food is allowed because it benefits the mind and body. Conversely, bad food is not allowed because it will damage the mind and body. The research method used was descriptive qualitative research methods. Data obtained from a variety of literature that discusses The Effects of Haram Food on Human Emotional and Spiritual Intelligence Levels, both in the form of books and journals. Data collection techniques by means of literature study, data analysis needed in library studies obtained from a number of references in the form of books, journals, encyclopedias, documents and others that are considered to have a relationship and can support the solution of existing problems. Data was analyzed by using qualitative data analysis techniques. Halal food and haram both have a big influence on someone’s life, both influential for morals, peace of mind, and fulfillment of prayer. People who always fill themselves with halal food, then the morals will be good, his heart will be calm and his prayers will be answered. Conversely, people who fill themselves with haram food will be bad in character, their hearts will be sick, and their prayers will not answered.